Teacher to Researcher: Reflections on a New Action Research Program for University EFL Teachers (2018)
One of the current challenges facing many universities is how to support teachers in becoming researchers. This article discusses the experiences at a small private Chilean university of a new action research programme that was developed as a vehicle for helping teachers to become involved in research and write a research publication for peer-reviewed journals. We present findings from research into similar programmes about relevant factors for their success, describe the programme developed at the university with five English as a Foreign Language teachers in 2016, and discuss some reflections on this first year of the programme.